Synthesis and Toxicity Tests of N-Carbothioamide-3-(2,4- Dichlorophenyl)-5-(4-Hydroxy-3-Methoxyphenyl)Pyrazoline - Irfan, Muhammad; Meylina, Lisna; Ramadhani, Agung; Rusli, Rolan (Journal of Tropical Pharmacy and Chemistry, 2024)
Pyrazoline is an alkaloid compound which has various biological activities such as antibacterial, antifungal, antitumor and anticancer. The compound N-carbotioamide-3-(2,4-dichlorophenyl)-5-(4-hydroxy-3-methoxyphenyl)pyrazoline was successfully synthesized from the basic ingredients 2',4'-dichloro-4-hydroxy-3-methoxychalcone and thiosemicarbazide with sodium hydroxide catalyst at 80°C for 7 hours. The synthesized compound was characterized using 1H-NMR, 13C-NMR, and mass spectroscopy and had a yield of 28.03%. Based on the results of toxicity tests using the Brine Shrimp Lethality Test (BSLT) method, this compound has an LC50 value of 44.6 ppm and has the potential to be an antimicrobial compound.